Cross-sectional analysis of potential risk factors of the pineal gland calcification - Nazanin Jalali; Mohammadrasoul Dehghani Firouzabadi; Ali Mirshekar; Parvin Khalili; Amir reza Ravangard; Jafar Ahmadi; Pooya Saeed Askari; Zahra Jalali (BMC Endocrine Disorders, 2023)
Abstract The Pineal gland (PG) is the site of production of melatonin as an important central hormone in the body. It is not known yet whether PG calcification (PGC) is an age-associated physiological process or a pathologic condition caused by lifestyle-factors and metabolic-dysregulations. Here, we performed a cross-sectional analysis on 586 patients referred to have Computed Tomographic (CT) scans (above 15 years old), in the Ali Ebne Abi Taleb hospital radiology center in 2017–2018. Based on the CT-scans of the brain, the presence of PGC was recorded and a score of scale 0 to 6 (PGC_score) was calculated for its intensity based on the volume and the Hounsfield units of the calcified pineal. Logistic and ordered logistic regression tests were employed to determine potential risk factor of PGC and higher PGC_score, respectively, testing the factors age, sex, history of cardiovascular and metabolic diseases, smoking and opioid use. We found male sex (OR: 2.30 (95% CI:1.39–3.82) and smoking cigarettes (OR: 4.47 (95% CI:1.01–19.78)) as the main potential risk factors for the pineal gland calcification. For PGC_score, we found age to be dose-dependently associated with PGC_score only in patients aged below 63 (p-trend < 0.001). Stratifying for age, in patients < 63 years old, we found age, male sex (positive association) and dyslipidemia (negative association) as the main significantly associated factors of PGC_score. On the contrary, in patients aged >  = 63, cigarette smoking was the only significantly associated factor of higher PGC_score. In conclusion, our results indicate that at ages below 63, age, male sex and blood lipid are the main associated factors of higher PGC, but at ages above that, the lifestyle factor smoking is significantly associated with higher pineal gland calcification.